2019
DOI: 10.1002/brb3.1240
|View full text |Cite
|
Sign up to set email alerts
|

Success and failure of controlling the real‐time functional magnetic resonance imaging neurofeedback signal are reflected in the striatum

Abstract: Introduction Over the last decades, neurofeedback has been applied in variety of research contexts and therapeutic interventions. Despite this extensive use, its neural mechanisms are still under debate. Several scientific advances have suggested that different networks become jointly active during neurofeedback, including regions generally involved in self‐regulation, regions related to the specific mental task driving the neurofeedback and regions generally involved in feedback learning (Sitaram… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

1
26
0

Year Published

2019
2019
2022
2022

Publication Types

Select...
4
2
1

Relationship

2
5

Authors

Journals

citations
Cited by 56 publications
(27 citation statements)
references
References 71 publications
1
26
0
Order By: Relevance
“…In line with Sitaram et al's model, the dlPFC, lateral occipital cortex, and lateral thalamus were involved in NF control, whereas the ventral striatum was involved in reward processing. This finding aligns well with other empirical study of NF-related reward signals (Ramot, Grossman et al 2016, Shibata, Lisi et al 2019, Skottnik, Sorger et al 2019. In contrast to Sitaram et al's suggestion, the insula was not involved in reward processing but rather in NF control (Shibata et al 2019, Paret et al 2018.…”
Section: Consider Functional Neuroanatomy Of Neurofeedback Learningsupporting
confidence: 91%
“…In line with Sitaram et al's model, the dlPFC, lateral occipital cortex, and lateral thalamus were involved in NF control, whereas the ventral striatum was involved in reward processing. This finding aligns well with other empirical study of NF-related reward signals (Ramot, Grossman et al 2016, Shibata, Lisi et al 2019, Skottnik, Sorger et al 2019. In contrast to Sitaram et al's suggestion, the insula was not involved in reward processing but rather in NF control (Shibata et al 2019, Paret et al 2018.…”
Section: Consider Functional Neuroanatomy Of Neurofeedback Learningsupporting
confidence: 91%
“…Mental imagery is one of the most common strategies reported by participants training to control the neurofeedback signal and often explicitly suggested as a potential strategy by the investigators. For this reason, the same general networks related to self-regulation, emotion, and visual imagery are modulated during these neurofeedback interventions as discussed for the psychotherapeutic applications of mental imagery (124, 140, 141). As a crucial difference to conventional mental imagery approaches, neurofeedback training additionally entails providing information on a subcomponent of these networks to the participant.…”
Section: Mental Imagery-based Treatments and Implicated Brain Networkmentioning
confidence: 99%
“…This is usually achieved by training participants to increase brain activation in relevant areas during positive mental imagery (123125, 126, 142) or to decrease activation in areas responsive to negative affective stimuli (143, 144). While neurofeedback provides information on whether a mental strategy is effective in modulating the neural basis of an emotional state, it has also been shown that neurofeedback at the same time stimulates the reward system (141, 145, 146) thereby potentially reinforcing the desired neural target state additionally (see the study by Sitaram et al (147) for an overview on prominent theoretical accounts on the working mechanisms of neurofeedback).…”
Section: Mental Imagery-based Treatments and Implicated Brain Networkmentioning
confidence: 99%
See 1 more Smart Citation
“…Skottnik, L., Sorger, B., Kamp, T., Linden, D., & Goebel, R. (2019). Success and failure of controlling the real-time functional magnetic resonance imaging neurofeedback signal are reflected in the striatum.Brain and Behavior, 9(3), e01240.157AbstractOver the last decades, neurofeedback has been applied in variety of research contexts and therapeutic interventions.…”
mentioning
confidence: 99%